2022
DOI: 10.1111/1365-2745.13939
|View full text |Cite
|
Sign up to set email alerts
|

UV radiation doubles microbial degradation of standing litter in a subtropical forest

Abstract: 1. UV radiation has been recognized as a direct driver of litter decomposition by photodegrading organic matter in dryland ecosystems. However, the importance and mechanism of UV radiation on litter decomposition, especially on standing litter, in humid forest ecosystems remain unclear.2. We conducted a factorial experiment in a humid subtropical forest gap, manipulating the effects of UV radiation on the decomposition of standing litter under different microbial conditions.3. After 366 days of standing incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…In summer, UV radiation contributed to 9.88% of the mass loss, indicating its significant role in litter decomposition under sufficient sunlight. However, UV radiation did not significantly increase the mass loss rate in autumn and winter (Jiang et al, 2022). In addition, our study revealed that the mass loss during summer was significantly higher than that during winter, with K. caspia, A. sparsifolia, and P. euphratica experiencing increases of 4.3%, 9.6%, and 6.8%, respectively, due to seasonal variation (Figure 6).…”
Section: Effects Of Seasonal Variation On Decomposition In Hyper-arid...mentioning
confidence: 65%
See 1 more Smart Citation
“…In summer, UV radiation contributed to 9.88% of the mass loss, indicating its significant role in litter decomposition under sufficient sunlight. However, UV radiation did not significantly increase the mass loss rate in autumn and winter (Jiang et al, 2022). In addition, our study revealed that the mass loss during summer was significantly higher than that during winter, with K. caspia, A. sparsifolia, and P. euphratica experiencing increases of 4.3%, 9.6%, and 6.8%, respectively, due to seasonal variation (Figure 6).…”
Section: Effects Of Seasonal Variation On Decomposition In Hyper-arid...mentioning
confidence: 65%
“…Seasonal variations have been reported to affect litter decomposition rates (Berenstecher et al, 2020;Jiang et al, 2022;Dirks et al, 2010;Ma et al, 2017;Gao et al, 2023). Some studies suggest that light intensity seasonally affects litter decomposition due to stronger solar radiation in summer than in winter (Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Litter decomposition rate is not only affected by soil microbial communities, but also by solar radiation (Wang et al 2021a;Jiang et al 2022). Previous studies have proved that litter decomposition can be directly accelerated by solar radiation via photochemical mineralization, and indirectly via the encouraging process of biotic degradtion, known as photofacilitation, in many terrestrial ecosystems (Lee et al 2012;Austin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Page 16/ 24 We wish to express our thanks for the support received from the Castanopsis kawakamii Nature Reserve in Sanming City, Fujian province to allow us to collect samples. The authors wish to thank X.G.G., M.J.L., L.J., J.Y.…”
Section: Acknowledgmentsmentioning
confidence: 99%